2011
DOI: 10.1128/jvi.02529-10
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR+CD38+CD4+T Lymphocytes Have Elevated CCR5 Expression and Produce the Majority of R5-Tropic HIV-1 RNAInVivo

Abstract: Percentages of activated T cells correlate with HIV-؊ DR/38 subsets (P < 0.001 for both). Median HIV-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
81
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 48 publications
8
81
1
Order By: Relevance
“…Somewhat contrary to expectations, but consistent with previous observations from our group and others (13,22), we found total HIV DNA to be present in equivalent proportions across all resting/activated subsets before the commencement of ART (Fig. 2).…”
Section: Discussioncontrasting
confidence: 55%
“…Somewhat contrary to expectations, but consistent with previous observations from our group and others (13,22), we found total HIV DNA to be present in equivalent proportions across all resting/activated subsets before the commencement of ART (Fig. 2).…”
Section: Discussioncontrasting
confidence: 55%
“…25 Similarly, study of infection of resting cells has generally used the lack of expression of HLA-DR, CD25, and CD69 as markers of activation. 51 Infection of activated CD38 + CD4 + T cells in PBMCs in vitro and lymphoid tissue in vivo has been investigated 52 ; however, circulating CD38…”
Section: Discussionmentioning
confidence: 99%
“…51,52,58 In those latter studies, activated CD4 + T cells were compared to nonactivated CD4 + T cells, which presumably contained substantial proportions of naive CD4 + T cells, which contain approximately 10-fold less HIV-1 DNA than memory CD4 + T cells. 45,59 One study defined HLA-DR -CD25 -CD69 -as resting cells, 51 but we have found that this subset contains CD38…”
Section: Hiv-1 Dna In Non-gut-homing Cd4mentioning
confidence: 99%
“…The number of activated CD4 + T cells, as assessed in cervical mononuclear cell preparations, is increased during mucosal inflammation and may promote HIV replication (39), and the genital HIV RNA level itself is an independent predictor of sexual transmission (40). A recent report on cytobrush-derived cervical cells from HIV + women suggested that genital CD4 T cell activation was associated with CD4 T cell depletion (41).…”
Section: Discussionmentioning
confidence: 99%